Cortisol sanguíneo e qualidade de carcaças de frangos abatidos pelo método halal ou com insensibilização por eletronarcose - Mendes, Paulo Vinícius da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Brazil is the largest exporter and third largest producer of broiler chickens, prominent position due to the meet the demands of consumers markets with incisive requirements, with investments in environmental sustainability and animal welfare. The countries of Islam have considerable importance for Brazilian exports. This study aimed to assess blood cortisol and chicken carcass quality slaughtered by the Halal method - own service this market without stunning, as required by Islam and compare them to numb by electro, according to humanitarian normal slaughter. Serum levels of blood cortisol using a commercial kit was performed in chickens slaughtered in fridge with SIF in the southwest region of the state of Goiás, to assess the immediate stress, ie at the time of slaughter, and the experimental design was completely randomized. Also evaluated the quality of animal housing slaughtered by both methods, trying to identify skin changes, attachments, muscles, bones and joints that show non-compliance with the animal welfare standards, depreciating therefore the carcass quality. It was found that there was a statistical difference between the different methods of slaughter, presenting a lower stress level of the animals, the method Halal and higher quality castings with the use of prior stunning for electro, followed by automatic sangria. We conclude that the animal welfare point of view, both slaughter methods still offer challenges to be understood and overcome. The traditional method of killing seems to take better account of animal welfare provisions due to the use of stunning animals, although a number of tecnopatias can depreciate the quality of carcasses.

O Brasil é o maior exportador e terceiro maior produtor de frangos de corte, posição de destaque decorrente do atendimento das demandas de mercados consumidores que possuem exigências incisivas, com investimentos em sustentabilidade ambiental e bem-estar animal. Os países de religião islâmica têm considerável importância para as exportações brasileiras. Este trabalho teve por objetivo avaliar o cortisol sanguíneo e a qualidade da carcaça de frangos abatidos pelo método Halal – próprio ao atendimento desse mercado, sem insensibilização, conforme requerido pela religião islâmica e compará-los aos insensibilizados por eletronarcose, de acordo com normais humanitárias de abate. Foram realizadas dosagens séricas de cortisol sanguíneo utilizando kit comercial, em frangos abatidos em frigorífico com SIF na região sudoeste do estado de Goiás, para avaliar o estresse imediato, ou seja, no momento do abate, e o delineamento experimental foi inteiramente casualizado. Avaliou-se também a qualidade de carcaça dos animais abatidos por ambos os métodos, procurando identificar alterações da pele, anexos, musculatura, ossos e articulações que evidenciem o não atendimento das normas de bem-estar animal, depreciando, portanto a qualidade da carcaça. Verificou-se que houve diferença estatística entre os diferentes métodos de abate, evidenciando menor nível de estresse dos animais, pelo método Halal e superior qualidade de carcaças com a utilização de prévia insensibilização por eletronarcose, seguido de sangria automática. Conclui-se que do ponto de vista de bem-estar animal, ambos os métodos de abate ainda oferecem desafios a serem compreendidos e superados. O método tradicional de abate parece atender mais adequadamente os preceitos de bem-estar animal devido o emprego da insensibilização dos animais, embora uma série de tecnopatias possa depreciar a qualidade de carcaças.
Blood cortisol and carcass quality of broilers slaughtered by halal method or stunned by electronarcosis
Keywords: Animal welfare; Chicken; Cortisol; Halal; Electro; Carcass quality; Bem-estar animal; Frango; Cortisol; Halal; Eletronarcose; Qualidade de carcaça